1996
DOI: 10.1111/j.1526-100x.1996.tb00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Semiarid Landscapes in Australia. I. Restoring Productive Soil Patches

Abstract: A rehabilitation procedure designed to reestablish resource control processes in a degraded Acacia aneura woodland was successful in improving soil nitrogen and carbon content, exchange properties, and water infiltration rates. Soil respiration rates and soil fauna populations increased, and soil temperatures were moderated. The procedure comprised laying piles of branches in patches on the contour of bare, gently sloping landscapes, with the expectation that soil, water, and litter would accumulate in these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 21 publications
3
87
1
Order By: Relevance
“…Insights into how such feedbacks are initiated, perpetuated, and manifested at different scales is currently the weak link in our ability to devise sustainable restoration strategies (Tongway and Ludwig 1996;Manu et al 1999). The ultimate challenge will be linking an ecohydrological understanding with the socioeconomic drivers of degradation (Reynolds 2001).…”
Section: What Ecohydrological Feedbacks Play a Role In Rangeland Degrmentioning
confidence: 99%
“…Insights into how such feedbacks are initiated, perpetuated, and manifested at different scales is currently the weak link in our ability to devise sustainable restoration strategies (Tongway and Ludwig 1996;Manu et al 1999). The ultimate challenge will be linking an ecohydrological understanding with the socioeconomic drivers of degradation (Reynolds 2001).…”
Section: What Ecohydrological Feedbacks Play a Role In Rangeland Degrmentioning
confidence: 99%
“…They ascribe this effect to the fact that soil biota decrease the amount of nitrogen in its more mobile form as nitrate and lead to an immobilization and storage of nitrogen in the increasing microbial biomass. For brushpacks Ludwig & Tongway (1996a) report an increase in organic carbon and nitrogen after 3 years under a brushpack treatment conducted in the semi-arid woodlands of Australia but only significant within the first 1 cm depth. As expected, the "stones" treatment showed no significant effect on any of the examined soil parameters.…”
Section: Effect Of Active Treatments On C/n Ratiomentioning
confidence: 98%
“…2). Several studies have shown that inadequate soil water storage is the major limiting factor for the sapling establishment in semiarid areas (Haase and Rose, 1993;Whisenant et al, 1999;South, 2000;HuesoGonzález et al, 2015;Muñoz-Rojas et al, 2016c), and others have reported new techniques needed to increase the AWC in dryland soils (Tongway and Ludwing, 1996;Shachak et al, 1998). Ros et al (2006) showed that the addition of amendments (urban organic waste, green waste, manure, and sewage sludge) favored the development of vegetation cover in Spain because of increased soil moisture.…”
Section: Available Water For Plants and Their Impact On Vegetation Esmentioning
confidence: 99%